2012
DOI: 10.1038/ng.1110
|View full text |Cite|
|
Sign up to set email alerts
|

Ascorbic acid prevents loss of Dlk1-Dio3 imprinting and facilitates generation of all–iPS cell mice from terminally differentiated B cells

Abstract: The generation of induced pluripotent stem cells (iPSCs) often results in aberrant epigenetic silencing of the imprinted Dlk1-Dio3 gene cluster, which compromises the cells’ ability to generate entirely iPSC-derived adult mice (“all-iPSC mice”). Here, we show that reprogramming in the presence of ascorbic acid attenuates hypermethylation of Dlk1-Dio3 by enabling a chromatin configuration that interferes with binding of the de novo DNA methyltransferase Dnmt3a. This allowed us to generate all-iPSC mice from mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
246
5
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(270 citation statements)
references
References 34 publications
7
246
5
4
Order By: Relevance
“…New mouse study from the Hochedlinger group showed that VC attenuated hypermethylation of Dlk1-Dio3 by disenabling intergenic differentially methylated region (IG-DMR) to recruit Dnmt3a (a DNA methyltransferase) in the progress of reprogramming. Interestingly, mature B cell-derived iPSCs were enabled to generate entire adult mice (all-iPSCs mice) when VC was added to the culture medium (Stadtfeld et al, 2012). The results are in agreement with a previous report that iPSCs with aberrant silenced Dlk1-Dio3 cluster failed to yield viable all-iPSCs mice (Stadtfeld et al, 2010).…”
supporting
confidence: 90%
“…New mouse study from the Hochedlinger group showed that VC attenuated hypermethylation of Dlk1-Dio3 by disenabling intergenic differentially methylated region (IG-DMR) to recruit Dnmt3a (a DNA methyltransferase) in the progress of reprogramming. Interestingly, mature B cell-derived iPSCs were enabled to generate entire adult mice (all-iPSCs mice) when VC was added to the culture medium (Stadtfeld et al, 2012). The results are in agreement with a previous report that iPSCs with aberrant silenced Dlk1-Dio3 cluster failed to yield viable all-iPSCs mice (Stadtfeld et al, 2010).…”
supporting
confidence: 90%
“…Dnmt3a and Dnmt3b have also been shown to be responsible for the methylation of most imprinted regions. Analyses of differentially methylated regions (DMR) indicated that aberrant DNA methylation is responsible for the transcriptional silencing of the Dlk1-Dio3 region in partially reprogrammed pluripotent iPSCs [20,42]. We found that, through targeting Dnmt3a and Dnmt3b, miR29b enhanced the expression of E-cadherin, Epcam, and Cldn3 while inhibiting the expression of mesenchymal genes including Snail, Zeb1, and Cdh2 during the reprogramming process.…”
Section: Discussionmentioning
confidence: 97%
“…This set comprises genes with well-known effects on the reprogramming process, such as Meg3 and Notch1. 33,34 Additionally, it contains 5 genes from the metallothionein family, all of them located within a 50 kb region on chromosome 16, therefore indicating an involvement of this loci in the reprogramming process. Taken together, our data suggest that in iPSCs, mostly stochastic expression of the genes that are rarely found in ESCs is observed, although some genes aberrantly expressed in iPSCs could be effectively used to qualify reprogrammed cells.…”
Section: Discussionmentioning
confidence: 99%